Mobile-Based Marketing Innovation as an Effort to Increase Tourist Interaction and Engagement in the Tourism Industry - Iswanto, Dedy; Irsyad, Ziqrurrahman; Istiqlal, Istiqlal (SCIENTIA: Journal of Multi Disciplinary Science, 2024)
This research aims to evaluate the influence of mobile-based marketing strategies on tourists' interaction with digital platforms in the tourism industry through a Systematic Literature Review (SLR) approach. The research process involved selecting literature from various academic databases, such as Google Scholar, Scopus, and DOAJ, with the keywords “mobile marketing,” “tourist interaction,” and “tourism” in the period 2014-2024. The research findings show that mobile technology significantly strengthens travelers' engagement with digital marketing tools, eases information access, and enhances a more personalized travel experience. Despite challenges related to data privacy and technological disruption, these strategies provide a competitive advantage for tourism destinations. This research also highlights the gaps in the application of mobile-based marketing in certain demographic segments, and the need for further research to formulate strategies that are inclusive and sustainable. Future research should focus on integrating digital marketing with traditional methods to create more meaningful and relevant tourism interactions.